'We talk, we do not have shame': addressing stigma by reconstructing identity through enhancing social cohesion among female sex workers living with HIV in the Dominican Republic. Issue 5 (4th May 2017) - Carrasco, Maria Augusta; Barrington, Clare; Kennedy, Caitlin; Perez, Martha; Donastorg, Yeycy; Kerrigan, Deanna
Abstract: This study explores social cohesion as a strategy used by female sex workers to address layered HIV and sex work-related stigma. Data derive from a thematic analysis of 23 in-depth interviews and 2 focus groups with female sex workers living with HIV enrolled in a multi-level HIV/STI prevention, treatment and care intervention in Santo Domingo, Dominican Republic. Drawing on Foucault's conceptualisation of modern power, discipline and resistance, we argue that social cohesion provides the psychosocial space (of trust, solidarity and mutual aid) to subvert oppressive societal norms, enabling the reconstruction of identity. Among study participants, identity reconstruction happened through the production, repetition and performance of new de-stigmatised narratives that emerged and were solidified through collective interaction. Findings highlight that enabling the collective reconstruction of identity through social cohesion – rather than solely attempting to change individual beliefs – is a successful approach to addressing stigma.